The impact of bullying on EFL students’ academic achievement at state Islamic universities in Indonesia - Muluk, Safrul; Habiburrahim, Habiburrahim; Dahliana, Syarifah; Akmal, Saiful (Englisia: Journal of Language, Education, and Humanities, 2021)
Issues and incidents of bullying may take place, regardless of time and place, notwithstanding at Islamic education institutions. This study is aimed at finding out types of bullying and their triggering factors taking place in the university classroom; examining steps taken by lecturers to anticipate and prevent classroom bullying; and analyzing the impact of bullying on EFL students’ academic achievement. This mixed-methods study involved 546 students and 30 lecturers of the English Language Education Department at three state Islamic universities in Indonesia; Universitas Islam Negeri Syarif Hidayatullah in Jakarta, Universitas Islam Negeri Sunan Kalijaga in Yogyakarta, and Universitas Islam Negeri Ar-Raniry in Banda Aceh. Both surveys and interviews were employed to collect the required data. The findings elucidate that physical, social, verbal, and racial are among the most common emergent bullying incidents the students experienced. Revealing the triggering factors of bullying, the data show that competition in academic and social life, differences in thoughts and appearances, lack of understanding of bullying meaning, and lack of regulation are pointed as the source of bullying. The findings also indicate that bullying influences students’ academic achievement; bullying incidents have driven their victims into four pathetic conditions: less confident, stressed, anxious, and passive. Some steps are applied by the lecturer to prevent and handle bullying; they are: providing classroom regulation, being a counselor for students, enforcing the regulation, and massive socialization.